Performance in the Chaordic Age: By Design or By Destiny? - L, Raymond; Jr, Forbes (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
This paper discusses the challenge of performance in an age characterized by high levels of both organizational and environmental uncertainty. Today, business, not-for-profit, and governmental institutions all find themselves besieged by difficult-to-predict periods of disorder and relative certitude. A new structural form, called the chaordic organization, has arisen as one means of operating in such a turbulent and indeterminate environment. This article will consider the chaos-certainty question, examine the concepts of performance and potential, deliberate whether performance can be influenced by calculated design measures, and look at current thinking related to motivation and its relationship to organizational performance. Additionally, a model of performance efficacy will be introduced, lessons learned provided, implications for the future presented, and a look offered at what might come next.